Recreational Demand for Fewa Lake: An Application of Travel Cost Method - Thapa, Arjun K (Economic Literature, 2016)
Economic valuation of non-market commodities like the recreational amenities provided by national parks, lakes, zoos and sanctuaries is complex and new in Nepal. In this study it is intended to analyze the recreational demand of Fewa Lake by using individual travel cost method. Fifty Nepali visitors were interviewed by administering close ended questionnaire schedule. Most of the respondents were urban unmarried males with secondary and above qualifications, earning a monthly income of around rupees ten thousand. The regression result shows cost of travelling, income, age, * education and location as the major determinants of demand for Fewa Lake’s recreational amenities. The consumer surplus was estimated to be Rs. 18.5 per Nepali visitor per trip. It can be inferred that a provision of entry fee along with quality enhancement would attract more visitors and generate revenue for this Lake. Economic Literature, Vol. XI (54-59), June 2013